I thought you were a woman! Men as gender specialists in agricultural research - Rahman, F. (International Livestock Research Institute, 2016)
When Fayzur Rahman started at WorldFish, people were astonished. They thought the gender specialist would be a woman. Previously they had seen only women working on gender issues. It’s not easy when he works with men; he tries to remove their misconceptions on gender. After a certain time they accept and follow his advice. For example they ask him if he cooks, and he tells them “Yes, I do so every day! It’s important to help your family.” After a while they tend to listen to him. Interview with Fayzur Rahman (WorldFish) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684